Effects of prosocial lyrics and musical production elements on emotions, thoughts and behavior. (July 2021) - Ruth, Nicolas; Schramm, Holger
Popular music with prosocial lyrics affects listeners' thoughts, emotions and behavior, yet little is known about the role played by the actual music in this process. This study focused on the interaction between the prosocial lyrics and the musical production elements, examining whether certain versions of a song can enhance the effect of prosocial lyrics on thoughts, emotions and behavior. Based on the general learning model and the reciprocal-feedback model of music perception, a laboratory experiment ( N  = 136) was conducted to test how listeners are affected by music with prosocial or neutral lyrics and by an electronic or an unplugged version of the music. For this purpose, an original song was composed and produced, using the same melodies and harmonies with varied lyrics and instrumentation. In a pilot study ( n  = 36), a version with acoustic instrumentation was rated as the most emotional and fitting, whereas an electronic dance version was rated as the least emotional and fitting. There was a significant interaction effect between the lyrics and the musical production elements: Those listening to the unplugged version with prosocial lyrics showed the most empathetic emotions. Prosocial lyrics also had an effect on prosocial thoughts but not on behavior.